2017
DOI: 10.1002/iid3.158
|View full text |Cite
|
Sign up to set email alerts
|

The hemochromatosis protein HFE 20 years later: An emerging role in antigen presentation and in the immune system

Abstract: IntroductionSince its discovery, the hemochromatosis protein HFE has been primarily defined by its role in iron metabolism and homeostasis, and its involvement in the genetic disease termed hereditary hemochromatosis (HH). While HH patients are typically afflicted by dysregulated iron levels, many are also affected by several immune defects and increased incidence of autoimmune diseases that have thereby implicated HFE in the immune response. Growing evidence has supported an immunological role for HFE with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 137 publications
(184 reference statements)
0
48
0
Order By: Relevance
“…Accordingly, the absence of HFE in cells' cytoplasmatic membrane as a consequence of p.C282Y substitution was previously shown to favor intracellular iron accumulation . In addition, considering that HFE is a protein belonging to the major histocompatibility complex (MHC‐I) family, we cannot exclude that OA‐associated HFE ‐hemochromatosis could also be related with a possible immune response to the absence of p.C282Y HFE in the cytoplasmic membrane . There is also a report in which hand OA prevalence is increased in heterozygotes (pC282Y); however a recent study showed no significant differences between the prevalence of OA in p.C282Y heterozygotes compared to general population .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Accordingly, the absence of HFE in cells' cytoplasmatic membrane as a consequence of p.C282Y substitution was previously shown to favor intracellular iron accumulation . In addition, considering that HFE is a protein belonging to the major histocompatibility complex (MHC‐I) family, we cannot exclude that OA‐associated HFE ‐hemochromatosis could also be related with a possible immune response to the absence of p.C282Y HFE in the cytoplasmic membrane . There is also a report in which hand OA prevalence is increased in heterozygotes (pC282Y); however a recent study showed no significant differences between the prevalence of OA in p.C282Y heterozygotes compared to general population .…”
Section: Discussionmentioning
confidence: 93%
“…33 In addition, considering that HFE is a protein belonging to the major histocompatibility complex (MHC-I) family, we cannot exclude that OA-associated HFE-hemochromatosis could also be related with a possible immune response to the absence of p.C282Y HFE in the cytoplasmic membrane. 77 There is also a report in which hand OA prevalence is increased in heterozygotes (pC282Y) 11 ; however a recent study showed no significant differences between the prevalence of OA in p.C282Y heterozygotes compared to general population. 78 Therefore, further studies regarding HFE recognition by the immune system are required.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, HFE protein is at the interface of iron metabolism and immune system linking HFE to antigen presentation by major histocompatibility complex class I (MHC-I) molecules [95].…”
Section: Interplay Between Iron Metabolism and Immune System In Tumormentioning
confidence: 99%
“…HFE generally regulates iron uptake into cells by competing with TF to bind TFR1. While low level of HFE leads to increased iron uptake, its high expression can diminish cellular iron uptake . K5 protein appears to degrade HFE in order to elevate cytosolic iron levels essential for lytic phase.…”
Section: Role Of Iron In Oncogenesis By Virusesmentioning
confidence: 99%